Listening to The Interpretative Voice of Pianists From The Past: Considerations regarding Practical Editions and Transcriptions (DAPesquisa, 2024)
This article aims to discuss the interpretative voice that makes itself present in the process of editing and arranging, discussing editorial queries and the act of transcribing after the idea that practical editions and transcriptions, as historical documents, not only figure as representatives of the performative conventions of a given time, but allow us to listen to the voice of these interpreters and editors and, therefore, are relevant when we face periods prior to coming of phonographic registration. At the end, the article addresses the transcriptions of a Bach chorale “Wachet auf, ruft uns die Stimme” made by Ferruccio Busoni, with the intent to contextualize, in a specific case, the reflections previously made.
Keywords: Transcription.; Practical Edition.; Bach.; Busoni.; Performative Conventions